Effect of ozone therapy on redox status in experimentally induced arthritis (Ozone Therapy Global Journal, 2011)
Controlled ozone administration has been shown to promote an adaptation to oxidativestress by increasing endogenous antioxidant systems. In the present study, the effectsof O2/O3 administration either prophylactically or therapeutically on the alterations ofoxidant status in adjuvant-induced arthritis in rats have been studied. Seven groupsof rats were used: 1) normal control group; 2) control arthritic group (21 days); 3) prophylacticozone group: arthritic rats received fifteen intra-rectal applications of O2/O3at 0.5, 0.7 and 1 mg/kg b.w. in a 5-6 mL volume starting one day before adjuvant inoculationand continued as five applications/week over 21 days; 4) oxygen group: receivedoxygen (vehicle of ozone) in a similar schedule to group 3; 5) control arthriticgroup (24 days); 6) therapeutic-ozone group: arthritic rats received 10 intra-rectal applicationsof O2/O3 at 0.5, 0.7 and 1 mg/kg b. w. in a 5-6 mL volume daily for 10 daysstarting fourteen days after adjuva nt i noculation; 7) oxygen-trea ted group: receivedoxygen in a similar schedule of group 6. The effect of O2/O3 administration was assessedby measuring: bloo d glutathione (GSH ), erythrocyte glutathione peroxidaseand catalase activities, serum levels of protein thiols (PrSH), malondialdehyde (MDA)and nitrite/nitrate (NO2/NO3), as well as serum ceruloplasmin activity (CP). The presentstudy showed that adjuvant-induced arthritis in rats caused a significant (p